Respuesta :
18[tex] x^{3} +9x[/tex]÷[tex] 6x^{2} [/tex]
=[tex] \frac{18 x^{3}+9x }{ 6x^{2} } [/tex]
=[tex] \frac{9x(2 x^{2} +1)}{6 x^{2} } [/tex]
=[tex] \frac{3(2 x^{2} +1)}{2x} [/tex]
=[tex] \frac{18 x^{3}+9x }{ 6x^{2} } [/tex]
=[tex] \frac{9x(2 x^{2} +1)}{6 x^{2} } [/tex]
=[tex] \frac{3(2 x^{2} +1)}{2x} [/tex]
we can first simplify the numerator which is 18x^3 + 12x – 3x into 18x^3 + 9x. The simplified numerator adds the the same terms which is 12x and -3x. In this case, we can factor 9x in the numerator into 9x ( 2x2 + 1). We can cancel 3x from the numerator and the denominator. Hence the final expression results to 3 ( 2x2 + 1) / 2x.